2020
DOI: 10.1002/ajpa.24170
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of subadult skeletal and dental development based on living and deceased samples

Abstract: Objectives A fundamental assumption in biological anthropology is that living individuals will present with different growth than non‐survivors of the same population. The aim is to address the question of whether growth and development data of non‐survivors are reflective of the biological consequences of selective mortality and/or stress. Materials and Methods The study compares dental development and skeletal growth collected from radiographic images of contemporary samples of living and deceased individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 73 publications
1
19
0
1
Order By: Relevance
“…The differing contexts of origin for the SVAD samples and the fact that it is comprised of data from deceased and living individuals do not seem to influence the range of values for indicators in each population. A recent study showed no differences in long bone lengths and dental development between the deceased (medical examiner's office context) and living (hospital/clinical context) individuals from the U.S. and South African samples [10]. Although these findings should be verified on the other SVAD samples, they suggest there is no bias in skeletal and dental indicators that is related to the type of collaborating institution, the context of origin of the individuals (forensic or clinical), or the type of medical image (CT scan or radiograph), and that these indicators could be compared across samples for anthropological research [28].…”
Section: Collaborations Contributions and Imaging Modalitiesmentioning
confidence: 97%
See 2 more Smart Citations
“…The differing contexts of origin for the SVAD samples and the fact that it is comprised of data from deceased and living individuals do not seem to influence the range of values for indicators in each population. A recent study showed no differences in long bone lengths and dental development between the deceased (medical examiner's office context) and living (hospital/clinical context) individuals from the U.S. and South African samples [10]. Although these findings should be verified on the other SVAD samples, they suggest there is no bias in skeletal and dental indicators that is related to the type of collaborating institution, the context of origin of the individuals (forensic or clinical), or the type of medical image (CT scan or radiograph), and that these indicators could be compared across samples for anthropological research [28].…”
Section: Collaborations Contributions and Imaging Modalitiesmentioning
confidence: 97%
“…These include one or several of the following limitations: relatively small samples [3,4], uneven age distributions [1], anatomically incomplete or taphonomically damaged skeletons, historic samples that do not accurately reflect contemporary growth and development or health [5,6], samples truncated to one type of indicator [7], and/or incomplete or inaccurate information on demographics, population affinity, or socio-economic status [1,6,8,9]. Therefore, the subadult material to use as reference material in forensic anthropology or for ontogenetic studies of modern populations is limited, if not questionable [10]. As evident with the Granada Collection [1] where infants younger than the age of one year old make up 80% of the subadult sample, available skeletal collections also often have unequal age distributions because of differential mortality risks in subadults.…”
Section: The Need For Contemporary Subadult Reference Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Children in the Maresh study were noted to be larger and heavier than children from other North American growth studies [ 99 ]. Other datasets of long bone measurements are available that do encompass different socioeconomic and geographic contexts [ 106 ], and have been used in anthropological studies [ 107 ]. However, they do not necessarily encompass the full ontogenetic range, include all long bones, or incorporate as much detail regarding lifestyles.…”
Section: Measuring Growth In Past Populationsmentioning
confidence: 99%
“…These studies are informative but building on them using tools such as DXA to investigate skeletal linear dimensions and proportions would allow for deep time comparisons of growth variability. Researchers are working to include a greater range of childhood experiences in modern skeletal studies [ 74 , 107 ]; however, there is room to grow in this research area.…”
Section: Bridging Measurements Past and Presentmentioning
confidence: 99%